2008
DOI: 10.1016/j.alcohol.2008.03.132
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and cerebral blood flow among older adults

Abstract: A substantial epidemiological literature now supports the existence of a J-or U-shaped association between alcohol consumption and a broad range cardiovascular health outcomes including stroke. Although it is well documented that alcoholics exhibit both global and regional cerebral hypoperfusion in the sober state, little is known regarding the effects of a broader range of alcohol consumption on cerebral blood flow (CBF). The present study employed positron emission tomography with H 2 15 O to assess quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 42 publications
1
20
3
Order By: Relevance
“…514 Heavy alcohol consumption can result in hypertension, hypercoagulability, reduced cerebral blood flow, and increased risk of atrial fibrillation. 493,498,500,513,515 A recent prospective cohort study among 43 685 men from the Health Professionals Follow-up Study and 71 243 women from the Nurses' Health Study 8 showed that alcohol intake had a J-shaped association for risk of stroke. A lower risk of stroke was found in women who were light drinkers, but women who drank Ն30 g of alcohol per day had a 40% increased risk of stroke (RR, 1.41; 95% CI, 1.07 to 1.88 for ischemic stroke; RR, 1.40; 95% CI, 0.86 to 2.28 for hemorrhagic stroke).…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…514 Heavy alcohol consumption can result in hypertension, hypercoagulability, reduced cerebral blood flow, and increased risk of atrial fibrillation. 493,498,500,513,515 A recent prospective cohort study among 43 685 men from the Health Professionals Follow-up Study and 71 243 women from the Nurses' Health Study 8 showed that alcohol intake had a J-shaped association for risk of stroke. A lower risk of stroke was found in women who were light drinkers, but women who drank Ն30 g of alcohol per day had a 40% increased risk of stroke (RR, 1.41; 95% CI, 1.07 to 1.88 for ischemic stroke; RR, 1.40; 95% CI, 0.86 to 2.28 for hemorrhagic stroke).…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…On the other hand, chronic application of grape polyphenols did not affect vascular function in the brachial artery in healthy men [43]. In a PET study of resting cerebral blood flow in 51 men and 35 women [44], an inverted J-shaped relationship between alcohol consumption and cerebral blood flow was found with a global cerebral blood flow greater in the lightest alcohol consumption group (<1 per week) and lower in the heaviest (>15 per week). In contrast, our study demonstrated no effect of chronic consumption of small amounts of polyphenol-rich red wine on cerebral blood flow velocity.…”
Section: Discussionmentioning
confidence: 99%
“…685,686 Heavy alcohol consumption can result in hypertension, 687693 hypercoagulability, reduced cerebral blood flow, 694 and an increased risk of AF. 662,668,695698 Studies show an increased risk for stroke in hypertensive patients who consume alcohol, as well as poor BP control in heavy drinkers with hypertension.…”
Section: Less Well-documented or Potentially Modifiable Risk Factorsmentioning
confidence: 99%